2013
DOI: 10.1016/j.dental.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of several dental substrates by non-thermal, atmospheric plasma brush

Abstract: Objective The purpose of this study was to reveal the effectiveness of non-thermal atmospheric plasma brush in surface wettability and modification of four dental substrates. Methods Specimens of dental substrates including dentin, enamel, and two composites Filtek Z250, Filtek LS Silorane were prepared (~2 mm thick, ~10 mm diameter). The prepared surfaces were treated for 5–45 s with a non-thermal atmospheric plasma brush working at temperatures from 36 to 38 °C. The plasma-treatment effects on these surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
132
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(155 citation statements)
references
References 37 publications
9
132
0
14
Order By: Relevance
“…The chemical changes include the improvement of the surface wettability and forming a functional group such as hydroxyl brought to the surface after exposure to plasma. 15 In this study, although NTP alone did not showed improvement of shear bonding strength, the combination of NTP with sandblasting showed signiflcantly higher value. This is maybe due to thermoplastic resin's high degree of crystallinity, 1,9-11 the NTP alone is not enough to improve the bonding strength between TDBRs and relining resin.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The chemical changes include the improvement of the surface wettability and forming a functional group such as hydroxyl brought to the surface after exposure to plasma. 15 In this study, although NTP alone did not showed improvement of shear bonding strength, the combination of NTP with sandblasting showed signiflcantly higher value. This is maybe due to thermoplastic resin's high degree of crystallinity, 1,9-11 the NTP alone is not enough to improve the bonding strength between TDBRs and relining resin.…”
Section: Discussionmentioning
confidence: 91%
“…3) Sandblasting (SB) 50 μm alumina particles, treatment for 15 seconds with a pressure of 0.28 MPa at a distance of 20 mm perpendicular to the treated surface. 4) Sandblasting and nonthermal plasma (SB + NTP) combined treatment of sandblasting for 15 seconds followed by nonthermal plasma for 5 minutes at a distance of 10 mm perpendicular to the treated surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O tratamento com plasma é uma tecnologia "limpa" e "eficaz", em que as propriedades internas dos materiais podem permanecer inalteradas ou preservadas após o tratamento 5 . Plasmas não térmicos ou ainda plasmas atmosféricos são gases parcialmente ionizados, que contêm partículas altamente reativas, incluindo átomos eletronicamente excitados, moléculas, íons e espécies de radicais livres, cuja fase gasosa permanece próxima da temperatura ambiente 5,6 .…”
unclassified
“…Plasmas não térmicos ou ainda plasmas atmosféricos são gases parcialmente ionizados, que contêm partículas altamente reativas, incluindo átomos eletronicamente excitados, moléculas, íons e espécies de radicais livres, cuja fase gasosa permanece próxima da temperatura ambiente 5,6 . Dependendo da composição química do plasma ou gás, estas espécies altamente reativas podem reagir com a superfície, limpando, causando uma erosão (etching), combinando-se com a mesma e formando uma fina camada de recobrimento por plasma, e, desta forma, alterar as características da superfície 6,7 .…”
unclassified